Inter-individual variability in propofol pharmacokinetic/pharmacodynamic (PK/PD) model – a sensitivity analysis - Chang, J. J.; Syafiie, S.; Raja Ahmad, Raja Mohd Kamil; Lim, T. A. (Scholars Academic and Scientific Publisher, 2016)
Inter-individual variability is a major challenge to guarantee adequate anaesthesia in patients across the population. This variability can occur as a result of patient physiology (e.g. age and weight), variations in the pharmacokinetic (PK) process and differences in the pharmacodynamic (PD) function. For a safe and effective drug administration, it is important to recognise which and when these factors of variability cause a higher uncertainty on depth of anaesthesia. This study aimed to quantify the influence of these input factors on the uncertainty in Bispectral Index (BIS). In this study, Sobol’ variance-based sensitivity analysis was performed on Schnider PK/PD model. Nine factors were evaluated: age, body weight, height, V1, V3, Cl1, Cl3, Ce50, and γ. The importance of these factors were ranked according to their total sensitivity indices. It was found that Ce50 has the most determining role on BIS prediction. γ is a significant factor during the induction phase. The PD model alone was found to responsible for 70% to 90% of BIS uncertainty during the maintenance phase. The variability of height has negligible influence on BIS prediction and can be omitted from the PK/PD model.